Description of Aspirations of Citizens Learning Computer Operator Skills Training at Job Training Center (BLK) Payakumbuh City - Intan Permata Sari; Syafruddin Wahid; Vevi Sunarti (Universitas Negeri Padang, 2019)
This research was background by the high learning outcomes of student, which is presumably because of the learning aspirations of high learning citizens in participating in the computer operator skills Balai Latihan Kerja (BLK) Payakumbuh city. This research purpose to (1) describe the aspirations of learners to achieve the goals, (2) to describe the aspirations of the studying people from the desire to participate in the training, and (3) to describe the aspirations of the studying citizens with regard to resolve. This type of research is descriptive quantitative. The population in this research is the residents learn the skills of computer operator Balai Latihan Kerja (BLK) Payakumbuh city which amounted to 32 people. Samples were taken as much as 63%. The sample is 20 people. The sampling technique used cluster random sampling. Data collection techniques used are questionnaires, while the data collection tool using questionnaires. Data analysis techniques use the percentage formula. The results of the study showed that: (1) the aspirations of the villagers to achieve high ideals, (2) the aspsirations of the learners from the desire to participate in training activities are quite high, and (3) the aspirations of the studying residents with regard to determination in training activities as well high.Keywords: Aspiration, Students, Training